Pacientes en estado vegetativo persistente y problemas bioéticos asociados - González Estrada, Allan (2012)
In the present paper i shall review concepts as coma, vegetative state, locked-in syndrome and minimal consciousness state. From a philosophical and neuroscientific base we will explain some of the consciousnesssoft problem and base on this the brain areas that would be affected in coma and vegetative state patients. The last part of the paper shall cover the ethical and bioethical aspects of the issues related with coma patients and consciousness problems.